2019
DOI: 10.1111/jora.12438
|View full text |Cite
|
Sign up to set email alerts
|

How Is Religiousness Associated With Adolescent Risk‐Taking? The Roles of Emotion Regulation and Executive Function

Abstract: Existing literature has demonstrated an association between higher adolescent religiousness and lower risk‐taking via higher self‐regulation. This study sought to elucidate the roles of emotion regulation and executive function as parallel mediators in the link between religiousness and risk‐taking in a sample of 167 adolescents (mean age = 14.13 years, 52% male, 82% White at Time 1). Longitudinal results across three waves utilizing structural equation modeling indicated higher religiousness was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
(64 reference statements)
1
10
0
3
Order By: Relevance
“…One study reported a significant link between religiousness and executive functioning in an adult sample (i.e., accuracy and reaction time on Stroop task; Inzlicht, McGregor, Hirsh, & Nash, 2009). However, other studies demonstrated nonsignificant associations between religiousness and inhibitory control performance among adolescents (Holmes et al, 2019) or behaviors that are thought to be closely related to executive functions such as impulse control, organization, and strategic planning among adults (Wain & Spinella, 2007).…”
Section: Religiousness and Self-regulation Dimensionsmentioning
confidence: 99%
“…One study reported a significant link between religiousness and executive functioning in an adult sample (i.e., accuracy and reaction time on Stroop task; Inzlicht, McGregor, Hirsh, & Nash, 2009). However, other studies demonstrated nonsignificant associations between religiousness and inhibitory control performance among adolescents (Holmes et al, 2019) or behaviors that are thought to be closely related to executive functions such as impulse control, organization, and strategic planning among adults (Wain & Spinella, 2007).…”
Section: Religiousness and Self-regulation Dimensionsmentioning
confidence: 99%
“…Así, el entrenamiento de mindfulness o atención plena mejora la capacidad de regular las emociones, además de dirigir el acto cognitivo hacia metas trascendentes (Taren et al, 2017). En adolescentes, la autorregulación de las emociones y la función ejecutiva fueron consideradas simultáneamente para predecir conductas de riesgo asociadas a funciones ejecutivas, las cuales facilitan la regulación de las emociones asociadas a decisiones de menor riesgo, favorecidas por la actividad E/R (Holmes et al, 2019).…”
Section: Un Atisbo De Cambios Electrofisiológicos En La E/runclassified
“…Es una zona de asociación de alta complejidad que está involucrada con el aprendizaje de normas y la inhibición cognitiva, es decir, el control cognitivo y la anticipación de la expresión psicoafectiva (Kandel et al, 2013). Los mecanismos de control constatados en personas que desarrollan el contexto E/R pareciera que se ven muy reguladas, por lo cual esta zona es muy activa en los adolescentes que desarrollan actividad de mayor autocontrol, como mencionara Holmes et al (2019). No obstante, si bien existe evidencia de que es una zona que se activa funcionalmente con la estimulación E/R, no hay resultados concluyentes de cambios neuroanatómicos vinculados con la sustancia gris, así como de otras zonas que pudieran experimentar un crecimiento por la sobreestimulación, debido a la utilización de diversas técnicas de evaluación, algunas no comparables entre sí (Elk y Snoek, 2020).…”
Section: Un Atisbo De Cambios Electrofisiológicos En La E/runclassified
See 1 more Smart Citation
“…Numerous studies suggest that religiosity has a significant influence on adolescent behavior ( Salas-Wright et al, 2017 ; Holmes et al, 2019 ; James and Ward, 2019 ). However, according to some authors, “If researchers use only one domain of religiosity, they likely will fail to capture the collective influence of religiosity on risky sexual behavior” ( Smith, 2015 , p. 51).…”
Section: Introductionmentioning
confidence: 99%